Comparison of glulam beam-to-beam connections with round dovetail and half-lap joints reinforced with self-tapping screws. (10th December 2019) - Li, Hongmin; Lam, Frank; Qiu, Hongxing
Highlights: The RD joint with STSs was proposed to improve the behaviour of spliced beams. The mechanical properties of RD and HL joint with STSs were studied experimentally. The ultimate bending capacity of spliced beams with HL reaches 75% of intact beams. The spliced beams have significant lower variability compared to the intact beams. Abstract: In this paper, the flexural performance of glulam beam-to-beam connections with two types of joint reinforced by self-tapping screws (STSs) was compared. 10 reference intact beams, 10 beams with half-lap (HL) joint reinforced by STSs and 10 beams with round dovetail (RD) joint reinforced with STSs were experimentally investigated under four-point loading. Experimental results of the tested specimens were presented in terms of failure mode, ultimate strength, moment/rotational angle relationship and ductility. The findings indicated that both the failure mode of the joints with HL and RD presented ductility to some extent, compared with the brittle failure of intact glulam beam. The results in terms of ultimate moment capacity were fitted with different distributions. The 5th percentile value of the capacity of HL joint and RD joint obtained from different distributions could reach 75.8–76.7% and 75.9–77.5% of that of the intact beams, respectively. In addition, the spliced beams with RD joint had a higher stiffness. Moreover, the average ductility ratio of the spliced beams with RD was 14% lower than the value of the spliced beams with HL. Furthermore, both of the HL spliced beams and RD spliced beams have significant lower variability compared to the intact beams which further facilitates the application of these joints.